Association of Demographic Profiles with RT-PCR Test Results for Covid-19 Patients during First Wave of Pandemic: A Retrospective Cross-Sectional Study from Dedicated Laboratory of Manikgonj District of Bangladesh - Ahmed, Imtiaz; Akhtaruzzaman, Muhammod; Samad, Khurshida; Quadir, Rukhsana; Rabin, Nadia (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: RT-PCT test for Covid-19 is the most widely used test during the pandemic. Objectives: The purpose of the present study was to see the status of RT-PCR test for Covid-19 during first wave of pandemic in Bangladesh at a dedicated hospital outside Dhaka city. Methodology: This retrospective cross-sectional study was conducted in the Department of Microbiology at Colonel Malek Medical College, Manikgonj, Bangladesh from November 2020 to April 2021 for a period of six months. The suspected cases of covid-19 patients or patients who had the history of contact with the confirmed cases of Covid-19 patients were advised by the clinician to do the test. RT-PCR for Covid-19 test was performed and results were recorded with their age and gender. Results: A total number of 6678 cases were recruited for this study. The mean age with SD of positive and negative were 42.6±17.32 years and 40.98±18.78 years respectively (p=0.023). The male and female ratio was 1.8:1 (p=0.004). Out of 668 positive cases of Covid-19 patients most of them were from urban area which was 464(9.1%) cases during this pandemic (p=0.000). Out of 675 cases of having history of travel, Covid-19 was positive in 43(6.4%) cases. Again, 6003 patients were without travel history and among these 625(10.4%) cases were Covid-19 RT-PCR positive (p=0.001). Conclusion: In conclusion young adult male patients are most commonly suffering with Covid-19 infection. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 132-136